Pengaruh Etika Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Karyawan Sebagai Variabel Intervening Pada Muhammadiyah Bisnis Center (MBC) Di Metro - Suwarto; Darmawan; Rafi Haritsandi (Jurnal Manajemen DIVERSIFIKASI, 2024)
This research aims to find out whether the Ethics variable has a direct effect on EmployeePerformance, whether the Employee Performance variable has a direct effect on WorkMotivation, whether the Employee Work Ethics variable has a direct effect on WorkMotivation and to find out the indirect effect of the Work Ethics variable has an indirecteffect on employee performance through Employee Work Motivation at the MuhammadiyahBusiness Center. The method used was a qualitative method and a quantitative method, thesamples were employees of the Muhammadiyah Business Center (MBC). The tool used isPath Analysis using the SPSS Application. Based on the research results, it shows that workethics has a direct positive and significant effect on work motivation. This shows that workethics is the most important element of marketing with an effort to satisfy consumers' wantsand needs. Work ethics has a direct positive and significant effect on employee performance.This shows that work ethics is the most important element of an organization in its efforts tosatisfy consumers. Work motivation has a direct positive and significant effect on employee performance. This shows that if work motivation is related to ability, activity, quality,quantity, collaboration, employee performance will be better. Work ethics indirectly has apositive and significant influence on employee performance, through work motivation. Thisshows that if work motivation in terms of form, character, disposition, morals, behavior,driving ideals is related to abilities, activities, quality, quantity, cooperation, the employee'sperformance will be better.